Syllabus Management System (SMS) / Lim Lay Poh - Lim , Lay Poh (2004)
In these early years of 21 century, information technology is playing an important role in our lives. Syllabus Management System develops especially to increase the quality of teaching and learning to bring a better experience in lecturing. Syllabus Management System that consists of note, assignment, marking, Plagiarism and forum modules is developed to help lecturer and tutor to manage courses on FSCIT. Note module provides a course template for lecturers. This module also develops a question bank for lecturer to store their exam, quiz or tutorial question. Lecturer can set up quizzes and tutorial for student more easily. Students can do the quizzes and tutorial for students more easily. Students can do the quizzes and tutorial online and the system will mark automatically the objective type question and auto calculates students' examnination marks. Lecturere can download the students' tutorial and mark. This module also provides a center to let lecturer publish their announcement and let student to view their lecturer announcement.The waterfall methodology with prototyping used in development of SMS Windows XP Professional is a development platform for SMS and have. NET framework. We use SQL Server 2000 in the system database development. The selected programming tool include HTML, Java Script, VB script and ASP. NET. While software application for SMS consist of Macromedia Dreamweaver MX and Microsoft Visual Studio. Net. With SMS, hopefully our country will have better quality of university graduates in the future.